Improving the Physico-mechanical and Degradable Properties of Thermoplastic Polymer with Modified Starch Blend Composites for Food packaging Applications - Zaman, Haydar; Khan, Ruhul Amin (Progress in Applied Science and Technology, 2021)
Plastics are an essential item of modern life and are used in many other applications such as food packaging, building components, mulching, and much more. Plastics are a subspecies of a type of material that is not degraded in the natural environment. Plastic shopping bags are manufactured from low-density polythene (LDPE) which causes ecological problems because most plastic ingredients have been in waste storage and underground for a long time. Meanwhile, several options have been considered to increase the use of biopolymers to reduce ecological problems. In this research, sago starch (SS) was treated with sodium trimetaphosphate. Sago starch was mixed with LDPE in varying levels of starch (10%-30 wt%) and the same amount of treated SS was mixed with LDPE using additives (glycerol/urea, and epolene wax) were compounded via melt mixing technique tracked by injection molded to form sheets. The reduced tensile strength percentage of the treated composite indicates that the good distribution and uniformity of SS in the LDPE was lower but more elongated at break than in the untreated composite. Treated SS composites also show less water absorption and degradation than untreated SS plastic composites. The application of the degradable composite as an eco-friendly packaging component can be effectively judged by its percentage loss in tensile strength and elongation at break by 30.7%, 44.6%, and 20.5%, 29.9% for untreated and treated composites, respectively, after 6 months of exposure to soil burial.